The Role Of The Creative Economy In Increasing Community Income In The Digital Era: PERAN EKONOMI KREATIF DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI ERA DIGITAL - Masitoh, Gustina; Nashoha, Anis; Fuadati, Nuril; Khasanah, Zuhrif (Green Engineering Society, 2025)
Abstract. The rapid development of information and communication technology, especially in the digital era, has transformed the global economic landscape and opened new opportunities for the creative economy sector. The creative economy, which emphasizes the use of ideas, creativity, and innovation, plays a vital role in increasing community income and generating employment. This article aims to explore the role of the creative economy in improving the welfare of Indonesian society, particularly amid the fast-paced digital transformation. The method used in this study is a literature review, examining various sources such as academic journals, books, official reports, and relevant online articles. The main discussion covers the impact of digitalization on creative economy actors, its contribution to community income, challenges and development strategies in the digital era, and the role of artificial intelligence in the creative economy. The findings show that digitalization expands market access, enhances competitiveness, and strengthens local cultural identity. However, the sector still faces challenges such as low digital literacy and limited access to capital. Therefore, collaborative support from the government, private sector, and community is essential in the form of digital skills training, infrastructure development, and access to financing. A digital-based creative economy is thus expected to become a driving force for inclusive and sustainable economic growth.